2008
DOI: 10.1007/s00417-008-0987-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective thrombophilia screening of patients with nonarteritic anterior ischemic optic neuropathy

Abstract: Our results indicate that thrombophilic disorders are associated with the development of NAION in specific subgroups of patients. Selective screening of young patients, subjects with a personal or family history of thromboembolism, and patients without cardiovascular risk factors may be helpful in identifying NAION patients with thrombophilic defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
2
14
0
4
Order By: Relevance
“…Acheson and M.D. Sanders describe seven cases in which there is an associated thrombophilic state and non-arteritic anterior ischemic optic neuropathy [19], and Kuhli-Hattenbach et al [39] conclude that thrombophilic disorders are associated with the development of N-AION in specific subgroups of patients. Since such a controversy in the literature is evident, our study, based on a quite large study group and a broad spectrum of thrombophilic risk factors, is aiming to illuminate any existing associations that have not been pointed out so far.…”
Section: Discussionmentioning
confidence: 97%
“…Acheson and M.D. Sanders describe seven cases in which there is an associated thrombophilic state and non-arteritic anterior ischemic optic neuropathy [19], and Kuhli-Hattenbach et al [39] conclude that thrombophilic disorders are associated with the development of N-AION in specific subgroups of patients. Since such a controversy in the literature is evident, our study, based on a quite large study group and a broad spectrum of thrombophilic risk factors, is aiming to illuminate any existing associations that have not been pointed out so far.…”
Section: Discussionmentioning
confidence: 97%
“…Since thrombophilic disorders do not seem to be the singular causal agent for RAO and in view of the high costs involved in comprehensive screening, it moreover seems both reasonable and justifiable to limit screening for thrombophilic disorders in patients with RAO to individuals whose risk is elevated, i.e. who had already experienced thromboembolic events at a young age or have a family history of thrombosis [13,14,15,16]. However, to date, only very few studies have attempted to investigate the role of few thrombophilic disorders in patients with RAO.…”
Section: Introductionmentioning
confidence: 99%
“…Several observations have suggested that thrombophilic disorders, such as elevated homocysteine, lipoprotein(a) and high frequency of Leiden mutation, may be pathogenetically relevant in the development of NAION by increasing the risk for venous thromboembolism (VTE) [2, 6, 7]. On the other hand, recent studies did not demonstrate an association between NAION and a wide range of thrombophilic risk factors [3].…”
Section: Discussionmentioning
confidence: 99%
“…These include small and crowded optic disks, angle closure glaucoma or other causes of markedly raised intraocular pressure, optic disk drusen and cataract extraction [4, 5]. In addition, reports of thrombotic tendencies in some patients with NAION have raised the question of whether there is a causative link between thrombophilia and NAION [2, 6, 7]. Here we present, to the best of our knowledge, the first case of NAION associated with combined protein S deficiency and heterozygosity for prothrombin G20210A mutation.…”
Section: Introductionmentioning
confidence: 99%